(untitled) (International journal of medical sciences, 2026)
Cancer is a complex pathological process that occurs as a result of uncontrolled changes in cells at the genetic and epigenetic levels. This article analyzes the main molecular mechanisms, structural and functional changes that occur at the cellular level in cancer development. Mutations of oncogenes and antitumor genes, cell cycle disorders, apoptosis evasion, angiogenesis and metastasis processes are covered based on scientific sources. The results of the article serve to better understand the pathogenesis of cancer and develop new therapeutic strategies.